Impact-Induced Seismic Activity on Asteroid 433 Eros: A Surface Modification Process - Richardson, James E.; Melosh, H. Jay; Greenberg, Richard (Science (American Association for the Advancement of Science), 2004)
High-resolution images of the surface of asteroid 433 Eros revealed evidence of downslope movement of a loose regolith layer, as well as the degradation and erasure of small impact craters (less than ~100 meters in diameter). One hypothesis to explain these observations is seismic reverberation after impact events. We used a combination of seismic and geomorphic modeling to analyze the response of regolith-covered topography, particularly craters, to impact-induced seismic shaking. Applying these results to a stochastic cratering model for the surface of Eros produced good agreement with the observed size-frequency distribution of craters, including the paucity of small craters.